Intestinal injury can be effectively prevented by Dunaliella salina in gamma irradiated rats. Issue 5 (May 2019) - Khayyal, Mohamed T.; El-Baz, Farouk K.; Meselhy, Meselhy R.; Ali, Gamila H.; El-Hazek, Rania M.
Abstract: Dunaliella salina (D. salina) is one of the most common microalgae that is used as human food. It is isolated from the salty lakes in El-Fayoum and Lake of Bardawil-Sinai in Egypt and can withstand very high concentrations of salt: The potentiality of D. salina, a unicellular biflagellate green alga to protect against intestinal injury induced after radiation exposure was studied. D. salina was given orally in doses of 100 and 200 mg/kg to male Wistar rats for 5 days before exposure to 6 Gray (Gy) gamma radiation and continued for a further two days. Rats were sacrificed 24 h later and intestinal segments were dissected out. One segment was examined histologically and another was used to prepare homogenates to assess relevant biochemical parameters reflecting intestinal injury. Radiation exposure led to a rise in the histological damage score, an increase in tissue tumor necrosis factor (TNF-α), interleukin (IL-1β) and thiobarbituric acid reactive substances (TBARS) but a reduction in tissue reduced glutathione (GSH) and in serum citrulline. Pretreatment with either dose of D. salina effectively reduced the severity of intestinal mucositis induced by gamma radiation.